Construction of a WMR for Trajectory Tracking Control: Experimental Results - R. Silva-Ortigoza; C. Márquez-Sánchez; M. Marcelino-Aranda; M. Marciano-Melchor; G. Silva-Ortigoza; R. Bautista-Quintero; E. R. Ramos-Silvestre; J. C. Rivera-Díaz; D. Muñoz-Carrillo (The Scientific World Journal)
This paper reports a solution for trajectory tracking control of a differential drive wheeled mobile robot (WMR) based on a hierarchical approach. The general design and construction of the WMR are described. The hierarchical controller proposed has two components: a high-level control and a low-level control. The high-level control law is based on an input-output linearization scheme for the robot kinematic model, which provides the desired angular velocity profiles that the WMR has to track in order to achieve the desired position (x*,y*) and orientation (φ*). Then, a low-level control law, based on a proportional integral (PI) approach, is designed to control the velocity of the WMR wheels to ensure those tracking features. Regarding the trajectories, this paper provides the solution or the following cases: (1) time-varying parametric trajectories such as straight lines and parabolas and (2) smooth curves fitted by cubic splines which are generated by the desired data points x1*,y1*,…,xn*,yn*. A straightforward algorithm is developed for constructing the cubic splines. Finally, this paper includes an experimental validation of the proposed technique by employing a DS1104 dSPACE electronic board along with MATLAB/Simulink software.